Oryeongsan suppressed high glucose-induced mesangial fibrosis - Yoon, Jung Joo (BMC Complement Altern Med, 2015)
BACKGROUND: The pathological change of kidney in diabetic nephropathy is represented hypertrophy, inflammation, and renal fibrosis. Oryeongsan, traditional oriental herbal formula, is widely used for the treatment of nephrosis, dropsy, and uremia. This study was examined whether Oryeongsan attenuate high-glucose (HG)-promoted rat mesangial cell fibrosis and matrix accumulation, major features of diabetic glomerulosclerosis. METHODS: Oryeongsan was mixed traditional herbal medicine, Alisma orientale Juz, Polyporus umbellatus Fries, Atractylodes macrocephala Koidez, Poria cocos Wolf and Cinnamomum Cassia Presl (5:3:3:1). Renoprotective role in diabetic nephropathy of Oryeongsan was evaluated by [(3)H]-thymidine incorporation, Western blot, RT-qPCR and immunofluorescence microscopy assay. RESULTS: Rat mesangial cell proliferation induced by HG was significantly accelerated, which was inhibited by Oryeongsan in a dose dependent manner. HG enhanced expression of fibrosis biomarkers such as collagen IV and connective tissue growth factor (CTGF), which was markedly attenuated by Oryeongsan. Oryeongsan increased HG-inhibited membrane type-1 matrix metalloproteinase expression (MT1-MMP) and MMP-2 promotor activity, whereas suppressed HG-induced tissue inhibitor of matrix metalloproteinase-2 (TIMP-2) expression. Moreover, Oryeongsan promoted extracellular matrix degradation through disturbing transforming growth factor β (TGF-β)–Smad signaling. This study further revealed that Oryeongsan ameliorated HG-induced mesangial inflammation accompanying induction of intracellular cell adhesion molecule-1 (ICAM-1) and monocyte chemoattractant protein-1 (MCP-1). Moreover, pretreatment of Oryeongsan inhibited NF-κB translocation in HG-exposed mesangial cell. CONCLUSION: These results demonstrate that Oryeongsan has protective effect against renal proliferation, fibrosis, and inflammation. Therefore Oryeongsan may be specific therapies targeting renal dysfunction leading to diabetic nephropathy.